Design of a new eco-hybrid cement for concrete pavement, made with processed mixed recycled aggregates and olive biomass bottom ash as supplementary cement materials. (5th December 2022) - Rosales, M.; Rosales, J.; Agrela, F.; Sánchez de Rojas, M.I.; Cabrera, M.
Abstract: The development of new cements made from waste and by-products as substitutes for traditional raw materials is a necessary approach to mitigate the harmful impacts of the construction industry. These impacts are mainly CO2 emissions and the consumption of energy and natural resources during construction. In this study, new eco-hybrid cements were formulated with Mixed Recycled Aggregates (MRA) from Construction and Demolition Waste (C&DW) and Olive Biomass Bottom Ash (BBA), processed to a powder fraction. Both MRA and BBA were applied in several mortar mixtures replacing cement. The feasibility of using these recycled materials in a combined way, as supplementary cement material and in substitution of aggregates, can be demonstrated. The study of physical, chemical, mechanical and more types of properties were carried out on the cements, showing the possibility of incorporating both processed waste in relevant percentages. This paper try to match the properties of conventional Portland cements, getting similar properties to CEM II A/L, which is the one commonly used for concrete pavements. An adequate processing applied to both recycled materials and the optimised dosages in which substitution rates were added, resulted in favourable properties. These results have allowed the development of an eco-hybrid cement for the manufacture of both mortar and concrete.